KEMAMPUAN KOMUNIKASI BELAJAR SISWA MELALUI MODEL TALKING STICK BERBASIS MEDIA ANIMASI - Wilson Sitopu, Joni; Dianti Siboro, Thiur; Annisa Batubara, Nur (Jurnal Metabio, 2023)
This study aims to determine whether there is an improvement in students' learning communication skills after implementing the Talking Stick model based on animation media on the Animal Kingdom topic in grade 10 of SMA YPK Pematangsiantar. The sample in this study was class X MIPA 3 as the experimental class, with 33 students who were given treatment using the Talking Stick model based on animation media, and class X MIPA 2 as the control class, with 33 students who were given treatment using lecture or conventional methods. This study was a quasi-experimental study. Data analysis was performed using normality tests, homogeneity tests, n-gain scores, and t-tests at a significance level of α = 0.05. The calculations obtained an average pretest score for the control class (X MIPA 2) of 40.96, and for the experimental class (X MIPA 3) of 43.15. The average posttest score for the control class (X MIPA 2) was 70.84, and for the experimental class (X MIPA 3) of 83.27. The t-test analysis for the data on students' learning communication skills yielded a t-sig = 0.000. The criterion is that if the sig. value is <0.05, then Ho is rejected. The significance value of equal variances assumed is 0.000, which is less than 0.05. Therefore, Ho is rejected and Ha is accepted. It can be concluded that there has been an improvement in students' learning communication skills using the Talking Stick learning model on the Animal Kingdom topic in grade 10 of SMA YPK Pematangsiantar.